J18 Team trust as a predictor of collective efficacy in female rugby players - Brown, Kate E (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
According to Bandura’s (1997) social cognitive theory, “the higher the sense of collective efficacy, the better the team performance”. Bandura also states that collective efficacy is greater than the sum of its individual self-efficacies due to it being influenced by other cognitive factors, including trust (1986, 1997, J Cog Psychother, 13, 158-166). Therefore, the purpose of this study was to investigate the influence of team trust on the construct of collective efficacy within a sport context. It is proposed that team trust is an important cognitive factor that may precede the relationship between collective efficacy and group performance. With institute ethical approval (BREO:33249-A-Nov/2023-47988-1), 21 female college rugby players voluntarily completed the four factor Team Trust Scale (Costa & Anderson, 2011. Eur J Work Org Psych, 20, 119-154) and the five factor Collective Efficacy Questionnaire for Sport (Short, Sullivan. & Feltz, 2005, Meas Phys Ed Ex Sci, 9, 181-202) to measure the correlation between levels of team trust and collective efficacy and determine if team trust is indeed a valid predictor of collective efficacy. Linear regression analyses were conducted and correlation coefficients calculated using Pearson’s correlation. It was predicted that a positive correlation would be shown between the two constructs and that team trust is a significant predictor of collective efficacy. Assuming a positive hypothesis, the study recommends that rugby teams and interdependent sport teams, generally, should develop a high-quality environment of trust both on and off the pitch, given its relationship with collective efficacy and subsequent impact on performance. Relatively little research has been carried out into the effect of intrateam trust within sport and, therefore, this study serves to widen the exploration of this construct and its impact on other social constructs such as collective efficacy and their impact on team performance.